Providing of insight and transcendental worldview in the training stories of Quran - Mohammad Hossein Mardani Nokandeh (پژوهش نامه معارف قرآنی, 2015)
One of The main conditions of success in any work, especially in great work of education or upbringing, is adopting of methods and procedures which helps a person in reaching of his goal and traveling in the path of perfection.Monotheisticinsight is the most important education and vision that Islam wants to give it to human.Quranwants toacquaintpeoplewith God and to give knowledge to people about him. There are many educational stories in Holy Quran that seeks to provide insight and transcendental worldview to human. The main question in this research is that how the training stories of quran assist the human to provide a true insight and transcendental worldview?The main purpose of this article is providing of an insight and transcendental worldview to human through resultsand achievements of educational Stories that areextracted from the Quran. Three main conclusion that can be extracted from the paper are:1-Quran is trying to provide accurate insight about the realities of the world and remove the veils of negligence from human eyes. 2-Also, Changing ofinsights, false beliefs and replacing of the correct beliefs and ideas are other achievements of quranic stories. 3- Finally, Providing of accurate insight through the man’s confrontation with the facts and providing of practical insight, makes changing in horizon of human visionduring operation (practical achievements)and he can reach to the truth.